2009
DOI: 10.1123/ijsnem.19.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on Quadriceps Muscle Pain during Acute Cycling Exercise in Low versus High Caffeine Consumers

Abstract: This experiment examined the effect of a moderate dose of caffeine on quadriceps muscle pain during a bout of high-intensity cycling in low- versus high-caffeine-consuming males. College-age men who were low (< or =100 mg/day; n = 12) or high (> or =400 mg/day; n = 13) habitual caffeine consumers ingested caffeine (5 mg/kg body weight) or a placebo in a counterbalanced order and 1 hr later completed 30 min of cycle ergometry at 75-77% of peak oxygen consumption. Perceptions of quadriceps muscle pain, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
2
34
2
Order By: Relevance
“…Administration of adenosine in humans has been shown to elicit muscle pain (Sylven, Beermann, & Jonzon, 1986) due to adenosine binding to A2 receptors. In previous studies, reduced leg pain with caffeine was revealed in men (Motl, O'Connor, & Dishman, 2003) and women (Gliottoni et al, 2009) during moderate cycling as well as during a 1.5 h trial performed by cyclists exercising in the heat (Ganio et al, 2011). However, gender differences in pain tolerance have been identified (Dao & LeResche, 2000), and there are little data examining changes in pain during fatiguing exercise, which merits further study of caffeine's effects on muscle pain in women.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Administration of adenosine in humans has been shown to elicit muscle pain (Sylven, Beermann, & Jonzon, 1986) due to adenosine binding to A2 receptors. In previous studies, reduced leg pain with caffeine was revealed in men (Motl, O'Connor, & Dishman, 2003) and women (Gliottoni et al, 2009) during moderate cycling as well as during a 1.5 h trial performed by cyclists exercising in the heat (Ganio et al, 2011). However, gender differences in pain tolerance have been identified (Dao & LeResche, 2000), and there are little data examining changes in pain during fatiguing exercise, which merits further study of caffeine's effects on muscle pain in women.…”
Section: Introductionmentioning
confidence: 90%
“…It also acts as an adenosine antagonist in the central nervous system (Davis et al, 2002) by inhibiting adenosine's actions to promote fatigue. In this capacity, caffeine seems to block the pronociceptive effects of A2 a receptors on sensory afferents (Gliottoni, Meyers, Arngrimsson, Broglio, & Motl, 2009) which alters individuals' perceptual response. Doherty and Smith (2005) reported that caffeine reduces rating of perceived exertion (RPE) during exercise which explained approximately 30% of increased performance in response to caffeine ingestion.…”
Section: Introductionmentioning
confidence: 98%
“…Caffeine can also reduce exercise-induced muscle pain [34,35], increase pleasure during exercise [36], and increase exercise enjoyment [37]. Importantly, caffeine can reduce perception of effort and exercise-induced muscle pain even at relatively low doses [38] and in habitual high caffeine consumers [39]. We should also consider that, in real-life applications, the efficacy of caffeine would be enhanced by its placebo effect [40] and associated changes in motorrelated cortical activity [41].…”
Section: Caffeine and Other Psychoactive Drugsmentioning
confidence: 99%
“…Caffeine acts as an adenosine antagonist on the CNS and changes the perception of pain during exercise. Previous studies reported that caffeine ingestion reduces leg muscle pain (Motl et al 2003(Motl et al , 2006Gliottoni and Motl 2008;Gliottoni et al 2009) during moderate and heavy cycling exercise, but this hypoalgesic effect disappeared with increases in performance during heavy to severe-intensity exercise (Jenkins et al 2008;Black et al 2015;Gonglach et al 2016). Astorino et al (2011) similarly determined that caffeine improved exercise performance during two sets of 40 repetitions of isokinetic knee extensions and flexions but did not change the RPE or pain perceptions in the leg.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, these studies have revealed that caffeine has no significant effect on untrained individuals performing high-intensity exercises for durations of 60-180 s, but that trained athletes may benefit from the ergogenic effects of caffeine. Previous studies have found that caffeine ingestion reduces both effort sense (Doherty and Smith 2005) and leg muscle pain (Motl et al 2003(Motl et al , 2006Gliottoni and Motl 2008;Gliottoni et al 2009) during exercise. In addition, caffeine could improve the ability of muscle to generate force by increasing motor unit recruitment (Kalmar and Cafarelli 1999;Kalmar 2005;Warren et al 2010;Black et al 2015).…”
Section: Introductionmentioning
confidence: 98%